British Defence Policy - Baylis, John. author. aut Link
XII, 169 p.
Keywords: This study of British defence policy argues that a "one-off" defence review is not enough but a regular process of defece reviews every five years provide a long-term strategic direction which, the author maintains, is lacking at present.